Cutaneous Rosai-Dorfman Disease After COVID-19 Vaccination: Rare Occurrence with Challenging Presentation - Harb, Zainab; Toorani, Zainab; Ali, Mahmood; Redha, Ali; Husain, Rola (Seminars in Musculoskeletal Radiology, 2025)
Rosai-Dorfman disease is an uncommon proliferation of non-Langerhans cell histiocytosis that mainly affects lymph nodes, although occasionally it can be associated or even present solely with extranodal involvement including skin and subcutaneous fat infiltration.We present a case of cutaneous Rosai-Dorfman disease that occurred at the site of administration of COVID-19 vaccine. The patient was a 13-year-old Bahraini girl who presented with a 1-year history of left upper arm pain and swelling that started after receiving the Pfizer vaccination for COVID-19. Clinically, the mass was medium-sized, tender, and nonmobile. Ultrasound and magnetic resonance imaging were suspicious for sarcoma. Ultrasound-guided biopsy revealed “subcutaneous panniculitis.” Excision of the mass revealed a multinodular infiltrate of the subcutaneous fat composed of distinctive large histiocytes, with characteristic emperipolesis, positive for S100, CD68, and OCT-2, consistent with Rosai-Dorfman disease. We present a case of cutaneous Rosai-Dorfman disease as a complication of COVID-19 vaccination that was challenging for the pathologist, radiologist, and clinician.
Keywords: Rosai-Dorfman disease; COVID-19; Pfizer vaccine; ultrasound; magnetic resonance imaging